Determinan Perencanaan Pajak Perusahaan Pertambangan di Indonesia - Agustina Agustina; Mie Mie; Syafira Firza (Politeknik Ganesha Medan, 2022)
This research aims to determine the effect of corporate governance as measured by institutional ownership, the proportion of independent commissioners, audit committee, and board of director also solvability, profitability, company size, growth opportunity, and capital intensity ratio on tax planning. The population in this research were all mining companies listed on Indonesia stock exchange for the 2015-2018 with the sampling technique used was purposive sampling. This type of research was causal associative, with data analysis method, namely confirmatory factor analysis and then continued with multiple regression analysis. The result of the factor test indicate that the audit committee is not a determinant of tax planning. Based on the results of regression analysis shows that simultaneously, institutional ownership, the proportion of independent commissioners, board of directors, solvency, profitability, company size, growth opportunity, and capital intensity ratio have an effect on tax planning. While partially, the results of the study indicate that institutional ownership, profitability, growth opportunity, and capital intensity ratio can be determinants that affect corporate tax planning. Meanwhile, the proportion of independent commissioners, board of directors, solvency, and company size partially not influence the company to do the tax planning. From results of this research, the government is expected will pay more attention to the grey area that can be used by companies as a gap to reduce tax payments which results in reduced state revenues.